'The First Act of Hostility': Beverley's Part in the Trial of Charles I. (1st January 2020) - English, Barbara
Abstract: The trial of King Charles I has in the last twenty years been discussed by many scholars. Much less attention has been paid to the evidence of the 33 witnesses summoned to the Westminster Court, yet what they said was the basis of the charges against the king. The first witness, William Cuthbert, was a Yorkshireman from Hull Bridge, Beverley. While the king and royalists alleged that the 'hostilities' of the Civil Wars had begun at the Beverley Gate, Hull, this prosecution witness claimed that the breaking, entering and possession of his house near Beverley was 'the first act of hostility that was committed in those parts.'